READ ALOUD SEBAGAI MEDIA PENGUATAN KARAKTER ANAK USIA DINI - Tika Yuniarti, S.E.,M.M; Suyanti; Putri Dian Wulandari; Marisa Amelia; Khusnul Hidayah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
A problem faced by early childhood education institutions is the low level of implementation of the read-aloud method as a means of character building in early childhood. Teachers tend to focus on academic skills such as reading and arithmetic, while the instilling of moral and social values ​​is not optimal. This community service activity aims to improve teachers' understanding and skills in implementing the read-aloud method creatively, interactively, and oriented towards strengthening character. The activity was carried out at the Ummu Salamah Kindergarten through stages of socialization, training, direct practice, and evaluation, involving teachers and children as active participants. The results of the activity showed an increase in teachers' abilities in expressive reading, selecting stories with moral value, and relating them to children's daily behavior. Children became more focused, enthusiastic, and understood the moral messages from the stories read. This activity proves that read-aloud is effective as a literacy medium as well as a means of instilling the values ​​of honesty, discipline, responsibility, and empathy from an early age. This program is expected to be implemented sustainably by teachers and parents to strengthen children's character through fun and meaningful learning.